2014
DOI: 10.5935/1808-8694.20140031
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Th17/Treg cell-mediated immunity imbalance in allergic rhinitis patients**Please cite this article as: Huang X, Chen Y, Zhang F, Yang Q, Zhang G. Peripheral Th17/Treg cell-mediated immunity imbalance in allergic rhinitis patients. Braz J Otorhinolaryngol. 2014;80:152-5, ****Study conducted at Third Hospital, Sun Yat-sen University, Guangdong, China

Abstract: The imbalance of peripheral Th17/Treg cells plays an important role in the pathogenesis of AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 13 publications
1
18
0
1
Order By: Relevance
“…In the study of Ciprandi and colleagues, serum IL-17 levels of AR patients were detected higher than those of controls and also, a positive correlation was indicated between serum IL-17 level and SS [ 28 ]. In another study, it was shown that serum IL-17 level in AR patients was higher while TGF- β level was lower than that in controls [ 29 ]. In our study and in many studies of literature mentioned above, it was shown that Th17 cells were active in a period when both SAR and PAR patients are symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Ciprandi and colleagues, serum IL-17 levels of AR patients were detected higher than those of controls and also, a positive correlation was indicated between serum IL-17 level and SS [ 28 ]. In another study, it was shown that serum IL-17 level in AR patients was higher while TGF- β level was lower than that in controls [ 29 ]. In our study and in many studies of literature mentioned above, it was shown that Th17 cells were active in a period when both SAR and PAR patients are symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…T h 17/T reg cell imbalance has been associated with airway allergic inflammation ( 23 , 24 ). A previous study demonstrated that the FOXP3 + T reg cell count in the nasal mucosa of allergic mice increased significantly following IB treatment ( 1 ), which was consistent with the current results of enhanced nasal mucosa FOXP3 mRNA expression following IB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a murine AR model, antibody mediated neutralization of IL-17 resulted in less eosinophil and neutrophil infiltration and lower Th2 and Th17 cytokine levels in nasal mucosa [ 16 ]. Elevated Th17 percentages and serum IL-17A levels have been reported in AR patients compared to controls [ 18 , 20 , 21 ] and a reduction of circulating Th17 cells after successful AIT has been reported [ 19 ]. A more recent study did not observe changes in Th17 numbers and function in AR patients during pollen season [ 22 ].…”
Section: Blood Cells In Armentioning
confidence: 99%